Evidence of Warming From Long-Term Records of Climate and Permafrost in the Hinterland of the Qinghai–Tibet Plateau - Zhou, Fujun; Yao, Miaomiao; Fan, Xingwen; Yin, Guoan; Meng, Xianglian; Lin, Zhanju (Frontiers in Environmental Science, 2022)
The Qinghai-Tibet Plateau (QTP) is characterized by its extreme climate and dominated by periglacial processes. Permafrost conditions vary greatly, and the recent changes on QTP are not well known in the hinterland. Here we examine changes in climate and permafrost temperatures in several different regions. Climate data were available from three weather stations from 1957-2019. Annual mean air temperature (Ta) has gradually increased at 0.031 to 0.039 °C/yr. Climate warming has been more rapid in the past two decades, particularly during the cold season (November to February). Precipitation has also been slowly increasing during the instrumental record. ril. Ground temperatures and active-layer thickness (ALT) have been investigated over ~20 years at five sites representative of the hinterland of QTP. These sites are located along the Qinghai-Tibet Highway, which crosses the permafrost zone traverses mountainous area and basin areas. Annual mean ground temperatures within the active layer (Tal ~1 m depth) indicate recent ground warming at all sites, at rates near 0.05°C/yr. The ALT at five sites has been increasing steadily by 2-9 cm/yr, and with an average of 4.6 cm/yr. The temperature near the permafrost table (Tps) has been increasing at 0.01 and 0.06 °C/yr, with an average of 0.03 °C/yr. Permafrost temperatures at 15 m depth (Tg) have been warming by about 0.01-0.02 °C/yr. In high mountainous areas where permafrost temperatures are low (e.g, KLS site), the annual mean Tg has warmed by nearly 0.02 °C/yr. The rate of permafrost warming rate at a basin site (BLH), with relatively high ground temperatures, was approximately 0.01 °C/yr. The GIPL2.0 model simulation results indicate that the annual mean permafrost temperature at 1 m depth at these sites will increase by 0.6-1.8 °C in next 100 year (to 2100), and that ALT will increase ~40-100 cm. We also discuss impacts of permafrost changes on the environment and infrastructure on QTP. This study provides useful information to understand observed and anticipated permafrost changes in this region, under different shared socio-economic pathways, which will allow for engineers to develop adaptation measures.